Innenansicht eines Raumes im Haus der Beiers in Port Moresby, in dem Batiken ausgestellt wurden (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Tapestry; Interior decoration; Port Moresby; Papua New Guinea; New Guinea